Structural Characteristics of Firn and Ice Cores Drilled at Mizuho Station, East Antarctica - Narita, Hideki; Maeno, Norikazu; Nakawo, Masayoshi (1978)
P(論文) Sizes, shapes and c-axis orientations of crystal grains as well as specific areas of grain boundaries and internal free surfaces were measured for firn and ice core samples of 147.5m length obtained in 1971 and 1972 at Mizuho Station (70°41.9'S, 44°19.9'E; 2230m), East Antarctica. Five critical depths were found at which some structural changes occurred. They were 8m, 30m, 55m, 70m and 110m. Their corresponding densities were 550,730,840,855 and 882kg・m^<-3>, respectively. The densities of 550 and 840kg・m^<-3> correspond to frequently reported figures at which the densification mechanism changes from mechanical packing of air voids to plastic deformation of ice grains, and from plastic deformation to shrinkage of closed-off air bubbles. The critical density of 730kg・m^<-3> (30m) was first pointed out by MAENO in 1974,who concluded that the bonding between ice grains reached its maximum or optimum state for packing at this density. The present analyses showed that air voids were gathered only at intersections of grain boundaries in the core samples at the critical density. The remaining two critical densities, 855kg・m^<-3> (70m) and 882kg・m^<-3> (110m), are related to alterations of mechanical stress fields; samples below 70m contained layers of small grains intermittently, and at depths deeper than 110m crystal sizes decreased, suggesting the presence of shear components. departmental bulletin paper